2014
DOI: 10.1098/rsbl.2014.0249
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for varying social strategies across the day in chacma baboons

Abstract: Strong social bonds can make an important contribution to individual fitness, but we still have only a limited understanding of the temporal period relevant to the adjustment of social relationships. While there is growing recognition of the importance of strong bonds that persist for years, social relationships can also vary over weeks and months, suggesting that social strategies may be optimized over shorter timescales. Using biological market theory as a framework, we explore whether temporal variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Indeed, a recent study at our site has found that individuals' grooming contributions can vary strategically across a day (Sick et al. ). In contrast, the role of maintaining long‐term (across years) and balanced relationships with other individuals may be to provide social support over longer time scales (Gomes et al.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, a recent study at our site has found that individuals' grooming contributions can vary strategically across a day (Sick et al. ). In contrast, the role of maintaining long‐term (across years) and balanced relationships with other individuals may be to provide social support over longer time scales (Gomes et al.…”
Section: Discussionmentioning
confidence: 95%
“…The main function of these relationships may be to negotiate access to resources, such as food in this study. Indeed, a recent study at our site has found that individuals' grooming contributions can vary strategically across a day (Sick et al 2014). In contrast, the role of maintaining long-term (across years) and balanced relationships with other individuals may be to provide social support over longer time scales (Gomes et al 2009;Silk et al 2010aSilk et al , 2012, with these relationships only exploited to provide short-term tolerance when the negotiating power of short-term relationships is exhausted, such as during periods of high foraging competition as in the experimental conditions.…”
Section: The Comparative Effect Of Social Bond Balance and Strength Imentioning
confidence: 95%
“…There is evidence that female Old World monkeys are capable of making strategic management decisions about their relationships as they maintain stable long-term relationships and more variable ones with different partners [12]. Furthermore, there is evidence that they can adjust their social relationships over short periods of time [13] and in response to seasonality [14][15] or demographic variation [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…I found two types of social grooming methods based on the trade-off between the number and strength of social relationships ( figure 1 ). One was ‘elaborate social grooming’, which was face to face and by phone (face to face (Pachur) [ 31 ] 1 and phone (Pachur) [ 31 ] (see footnote 1)), in kin and friends (mobile phone (friends and family) [ 32 ] 2 and short message service (SMS (friends and family)) [ 32 ] (see footnote 2)) and Chacma baboon social grooming (baboon group A and B) [ 6 ]. 3 This should be nearer to primitive human communications than the others.…”
Section: Discussionmentioning
confidence: 99%